2022
DOI: 10.1002/anie.202202866
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Metabolism in Humans

Abstract: Odorants are relatively small molecules which are easily taken up and distributed in the human body. Despite their relevance in everyday life, however, only a limited amount of evidence about their metabolism, pathways, and bioactivities in the human body exists. With this Review, we aim to encourage future interdisciplinary research on the function and mechanisms of the biotransformation of odorants, involving different disciplines such as nutrition, medicine, biochemistry, chemistry, and sensory sciences. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 123 publications
0
13
0
3
Order By: Relevance
“…To predict an odor, studies have mostly investigated the relationship between odorant molecule–receptor interactions, patterns of activity in the brain, and perceived odor. However, such odor–structure models underestimate the role of perireceptor events, which can affect the sensitivity and quality of the olfactory signal. Indeed, it has been shown that the enzymatic biotransformation of odorants in the olfactory epithelium or nasal mucus might affect peripheral olfactory processing. This enzymatic mechanism involves odorant metabolizing enzymes (OMEs), which catalyze the chemical conversion of odorants. A number of studies in insects, rodents, and rabbits have addressed the function of OMEs in the olfactory process. ,, Authors have demonstrated that OMEs metabolize the primary odorant molecule, resulting in its inactivation and termination of the olfactory signal. Strikingly, they also observed that the metabolites generated after conversion might be volatile and interact with odorant receptors. ,, Nagashima and Touhara showed that after exposing mice to benzaldehyde or acetyl-isoeugenol, their respective metabolites, benzyl alcohol and benzoic acid or isoeugenol, were detected in the mucus washed out from the nasal cavity .…”
Section: Introductionmentioning
confidence: 99%
“…To predict an odor, studies have mostly investigated the relationship between odorant molecule–receptor interactions, patterns of activity in the brain, and perceived odor. However, such odor–structure models underestimate the role of perireceptor events, which can affect the sensitivity and quality of the olfactory signal. Indeed, it has been shown that the enzymatic biotransformation of odorants in the olfactory epithelium or nasal mucus might affect peripheral olfactory processing. This enzymatic mechanism involves odorant metabolizing enzymes (OMEs), which catalyze the chemical conversion of odorants. A number of studies in insects, rodents, and rabbits have addressed the function of OMEs in the olfactory process. ,, Authors have demonstrated that OMEs metabolize the primary odorant molecule, resulting in its inactivation and termination of the olfactory signal. Strikingly, they also observed that the metabolites generated after conversion might be volatile and interact with odorant receptors. ,, Nagashima and Touhara showed that after exposing mice to benzaldehyde or acetyl-isoeugenol, their respective metabolites, benzyl alcohol and benzoic acid or isoeugenol, were detected in the mucus washed out from the nasal cavity .…”
Section: Introductionmentioning
confidence: 99%
“…Among proteins, odorant binding proteins (OBP) belong to the lipocalin family 9 and are potential odorant transporters. The nasal mucus contains many other proteins 10 , and recent studies have shown that among these proteins are enzymes metabolizing odorants [11][12][13][14][15] , which participate in olfactory peri-receptor events. These nasal proteins are involved in the protection of cells, including olfactory neurons, against reactive molecules (aldehyde, ester, sulfur compounds, etc.)…”
mentioning
confidence: 99%
“…Interestingly, the physicochemical properties of odorous molecules correlate with their perceived odor and can be used to predict the pleasantness of an odorant. 23 Moreover, one molecule can have different smells for different people, which can be due to genetic variations in the ORs, 24 different rates of odor metabolism, 25 the concentration of the odor, and in general the difficulty to describe an odor by words. 26 Similarly to aversive taste, aversive odors can alert from consuming spoiled food 27 or gas leakage.…”
Section: ■ Introductionmentioning
confidence: 99%